Colombia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2020)
This Selected Issues paper focuses on Venezuelan migration and the labor market. Over 2 million migrants have crossed the border from Venezuela and continue to join Colombia's labor market-which remains weak overall with rising unemployment and falling participation. There is so far little evidence of displacement effects on account of immigration, however, as the Colombian informal sector has capably absorbed most of the migrant inflow. A more granular view of Colombia's local labor markets does not show weaker employment outcomes in those that have received the most migrants. However, with many of these workers being highly skilled and attached to the informal sector, evidence of labor misallocation highlights the need to continue integration policies. The government is conducting efforts to accelerate the validation of Venezuelan degrees for easing the integration of professional migrants and high-school educated migrants who wish to continue their university studies in Colombia.